Editorial: Letter from the Editors - Heitmeyer, Wilhelm; Massey, Douglas S.; Messner, Steven F.; Sidanius, James; Wieviorka, Michel (International Journal of Conflict and Violence (IJCV), 2013)
- no abstract -